Replacement names for bees in the tribe Megachilini (Hymenoptera: Megachilidae) - Engel, Michael S. (Journal of Melittology, 2017)
Eight instances of homonymy are identified in the megachiline genera Coelioxys Latreille and Megachile Latreille, with replacement names established for the junior homonyms.  Coelioxys (Coelioxys) lethosyne Engel, new name, is proposed for C. simplex latefasciata Friese (nec Morawitz); C. (Liothyrapis) wuae Engel, new name, is proposed for C. albofasciata Wu (nec Radoszkowski); Megachile (Eutricharaea) hisarica Engel, new name, is proposed for M. dentata Rahman & Chopra (nec Friese); M. (Megachile) agnosta Engel, new name, is proposed for M. japonica Matsumura (nec Alfken); M. (Dasymegachile) schwimmeri Engel, new name, is proposed for M. mitchelli Raw (nec Gupta); M. (Creightonella) taftanica Engel, new name, is proposed for M. aurantiaca Rebmann (nec Friese); M. (Callomegachile) biseta austrina Engel, new name, is proposed for M. biseta australis Pasteels (nec Lucas); and M. (C.) ceratops Engel, new name, is proposed for M. monoceros Friese (nec Pallas).